The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcimb.2021.825427
|View full text |Cite
|
Sign up to set email alerts
|

Infant Pneumococcal Carriage in Belgium Not Affected by COVID-19 Containment Measures

Abstract: Streptococcus pneumoniae is an important and frequently carried respiratory pathogen that has the potential to cause serious invasive diseases, such as pneumonia, meningitis, and sepsis. Young children and older adults are among the most vulnerable to developing serious disease. With the arrival of the COVID-19 pandemic and the concomitant restrictive measures, invasive disease cases caused by respiratory bacterial species, including pneumococci, decreased substantially. Notably, the stringency of the containm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
4
32
1
2
Order By: Relevance
“…Studies in Belgium and Israel found no substantive reductions in prevalence pre- and post-NPIs, although in both our study and the Israel study pneumococcal prevalence was lower in one of the two time periods assessed. [4,5] Importantly, we observed a substantial decline in overall and capsular pneumococcal carriage density after the implementation of NPIs. In contrast, the Israel study found no difference in pneumococcal density pre- and post-NPI implementation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies in Belgium and Israel found no substantive reductions in prevalence pre- and post-NPIs, although in both our study and the Israel study pneumococcal prevalence was lower in one of the two time periods assessed. [4,5] Importantly, we observed a substantial decline in overall and capsular pneumococcal carriage density after the implementation of NPIs. In contrast, the Israel study found no difference in pneumococcal density pre- and post-NPI implementation.…”
Section: Discussionmentioning
confidence: 79%
“…[24] Only two studies have examined the impact of NPIs on pneumococcal carriage prevalence. [4,5] No substantive differences in carriage prevalence were observed in children pre- and post-implementation of NPIs in Belgium and Israel, but a decline in the prevalence of respiratory viruses was temporally associated with a decline in IPD in the Israel study. [4] Respiratory viruses increase pneumococcal carriage density, which contributes to transmission and disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from the few studies that have addressed this issue to date suggest that this does not seem to be the case. In Belgium and Israel, the prevalence of pneumococcal carriage in children aged <3 years was either unchanged during the pandemic or was only reduced slightly, although the IPD rates decreased markedly in the same age group ( Danino et al., 2021 ; Willen et al., 2022 ), Moreover, in Israel, colonization density and pneumococcal serotype distributions were similar to previous years ( Danino et al., 2021 ). The present study did not find a decline in pneumococcal carriage rates among children aged 24–60 months during the COVID-19 pandemic, but instead found a significant increase in rates in 2020 that remained high to June 2021.…”
Section: Discussionmentioning
confidence: 84%
“…It was initially assumed that the reduction in the incidence of IPD was due to reduced transmission of the bacteria resulting from the implementation of non-pharmaceutical interventions. Pneumococcus is commonly carried in the upper respiratory tract of young children, however, the prevalence of pneumococcal carriage in children was near normal levels during 2020-2021 [3,8]. This demonstrates that children were still being exposed to and acquiring pneumococcus but not getting sick.…”
Section: Introductionmentioning
confidence: 99%